Reforming the IMF: Lessons from modern central banking - Philipp Maier; Eric Santor (Bank of Canada, 2008)
The authors examine the institutional and governance framework of modern central banks to determine whether there are lessons that can be applied to the International Monetary Funds' (IMF's) institutional framework. Such a comparison is appealing for two reasons. First, both central banks and the IMF carry out tasks that can be described as delegated responsibilities. Second, while monetary policy has yielded mixed results in many countries for decades, it has recently enjoyed considerable success in reducing inflation. Substantial changes to the institutional frameworks of central banks have, at least partly, contributed to this success. This raises a simple question: can the lessons learned from modern central banking help to strengthen the governance of the IMF? The authors argue they can. Governance reform would enhance the IMF's decision-making process and make the Fund more transparent and accountable, thus improving the effectiveness of its main instruments surveillance and lending. The reforms proposed by the authors in this paper should not be viewed as immediately achievable goals; rather, they constitute a set of guiding principles for long-term governance reform.
Keywords: F3; 330; International topics; Zentralbank; Zentralbankrecht; Bankenpolitik; Bankenreform